EPIGRAPHIC DISCOURSE IN UNDERSTANDING THE QUR’AN FROM THE PERSPECTIVE OF ROBERT HOYLAND: Meneropong kajian Al-Quran melalui bukti Epigrafis - Mubarok, Achmad Sofiyul; Rohmaniyah, Inayah (HUNAFA Jurnal Studia Islamika, 2025)
This article focuses on the study of Epigraphy used to understand the Qur'ān. This article introduces epigraphy as an approach to understanding the Qur'an. In general, this article has the main objectives, namely: First, to describe the epigraphic discourse used by Hoyland to understand the Qur'an. Second, criticizing the discourse factors that encourage the emergence of Epigraphy in understanding the Qur'an and Third, analyzing the implications of Robert Hoyland's Epigraphic discourse. This article uses qualitative research employing Teun A. Van Dijk's critical discourse analysis theory to examine Robert Hoyland's social cognition in understanding the Qur'an through epigraphy. The results show that Epigraphy can be applied to understand the Qur'an by considering valid and credible evidence. Then the understanding of the Qur'an with Epigraphy is based on quite crucial factors, such as historical, continuity of the Qur'anic text, and interaction with other religions. In addition, Epigraphy also has implications for aspects of study, social, and practice. So that this article can be considered to have a contribution in the study of Al-Quran tafsir and multidisciplinary science.